2014
DOI: 10.1186/1472-6831-14-93
|View full text |Cite
|
Sign up to set email alerts
|

Facial morphometrics of children with non-syndromic orofacial clefts in Tanzania

Abstract: BackgroundOrofacial clefts (cleft lip/palate; CL/P) are among the most common congenital anomalies, with prevalence that varies among different ethnic groups. Craniofacial shape differences between individuals with CL/P and healthy controls have been widely reported in non-African populations. Knowledge of craniofacial shape among individuals with non-syndromic CL/P in African populations will provide further understanding of the ethnic and phenotypic variation present in non-syndromic orofacial clefts.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
17
0
4
Order By: Relevance
“…Although the ratio that we could found was not as high as that in the literature, a comparable gender distribution was also found in our study sample. The composition of the cleft sample with UCLP being more prevalent, and being more frequent on the left side, is in accordance with most reports [ 2 , 35 , 70 , 97 , 126 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although the ratio that we could found was not as high as that in the literature, a comparable gender distribution was also found in our study sample. The composition of the cleft sample with UCLP being more prevalent, and being more frequent on the left side, is in accordance with most reports [ 2 , 35 , 70 , 97 , 126 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, in non-avians, variation in midfacial outgrowth is determined primarily by differential growth of the maxilla (Young et al 2014). With direct relevance to human disease, it is notable that studies in human populations have shown the presence of broadening of the faces in patients affected by CL/P (Manyama et al 2014). In this study, we have characterized two mouse models of orofacial clefting that result from PBX loss-of-function in cephalic epithelium or CNCC-derived mesenchyme, both of which yield CL/P or CPO together with significant widening of the midfacial complex, establishing these mouse strains as unique models to dissect the complexities of orofacial clefting further.…”
Section: Discussionmentioning
confidence: 99%
“…The craniofacial skeleton is a complex trait and the full spectrum of genetic and environmental factors that contribute to its final structure remains largely unknown (Hallgrimsson et al, ; Powder and Albertson, ; Cole et al, ). Similarly, majority of the craniofacial structural birth defects have multifactorial etiology (Young et al, ; Manyama et al, ; Marcucio et al, ; Cole et al, ). The externally developing, transparent teleost embryos are excellent models to study the early events of head formation.…”
Section: A Mexicanus As a Model To Identify Craniofacial Birth Defectsmentioning
confidence: 99%
“…Cleft lip and /or cleft palate (CLP) are common birth defects that occur as a result of a failure in proper growth and fusion of the facial processes (Dixon et al, ; Manyama et al, ). Zebrafish has been identified as a model for CLP (Duncan et al, ).…”
Section: A Mexicanus As a Model To Identify Craniofacial Birth Defectsmentioning
confidence: 99%